POLICY IMPLEMENTATION OF A LINE LEARNING SYSTEM TO PREVENT THE SPREAD OF COVID-19 - Riswanda, Mike Fatiha Eka; Fauzi, Agus Machfud (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract : The positive online learning system policy is enforced for all levels of school, from kindergarten, elementary, junior high, high school to tertiary level. This policy was enforced due to the Covid-19 pandemic, for this reason an online learning system or distance learning was implemented as an effort to prevent the spread of Covid-19. The online learning system policy is deemed the right policy to be implemented in the face of the current pandemic because teachers and students do not meet face to face directly. Based on this background, the objectives of this study are 1) understanding and explaining the application of the online learning system policy in Mts Ketegan Sidoarjo, 2) analyzing the motives for implementing the online learning system policy at Mts Ketegan Sidoarjo. The method used in this study is a qualitative method, because to explain the research was carried out in depth. The theory used in this research is Schutz's theory of social motives. Schuzt introduced two motive terms, namely the